1999
DOI: 10.1007/s101470050034
|View full text |Cite
|
Sign up to set email alerts
|

Wheat germ agglutinin binding is a useful prognostic indicator in stomach cancer

Abstract: Background. Recent studies suggest that lectin binding activity is correlated with the metastasis and prognosis of several human carcinomas. Wheat germ agglutinin (WGA) is a lectin that recognizes mainly N-acetyl-glucosamin (GalNAc) and acetyl-neuramic acid. However, little is known about WGA expression in gastric carcinoma. The purpose of this investigation was to clarify the significance of WGA expression in human gastric carcinoma. Methods. WGA binding was examined immunohistochemically in 353 specimens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our results showed that both WGA and SBA reduced Bcl-2 and phospho-Bad levels, thus promoted cell apoptosis. Regardless of much neglects in normal tissues and cells, much efforts have been made to examine the apoptotic inducing effects of lectins in cancerous cells and consider it as potential anti-cancer agent (20, 21). WGA exposure induced chromatin condensation, nuclear fragmentation in human pancreatic carcinoma cells (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that both WGA and SBA reduced Bcl-2 and phospho-Bad levels, thus promoted cell apoptosis. Regardless of much neglects in normal tissues and cells, much efforts have been made to examine the apoptotic inducing effects of lectins in cancerous cells and consider it as potential anti-cancer agent (20, 21). WGA exposure induced chromatin condensation, nuclear fragmentation in human pancreatic carcinoma cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including those conducted in cancerous cell lines, were mainly focused on the pathological and apoptotic inducing effects of lectins (6, 20, 23). The upstream cell signaling pathways influenced by lectins were far less characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation